The complete chloroplast genome of the endangered plant Paphiopedilum wardii (Orchidaceae) - Lin Wang; Changhai Sui; Ying Wang; Jia Guo (Mitochondrial DNA. Part B. Resources, 2018)
Chloroplast (cp) genome sequences provide a valuable source for phylogenetic analysis, which becomes a popular tool for population and phylogeny in a recent report. Here, the complete chloroplast genome of the Paphiopedilum wardii has been reconstructed from the whole-genome Illumina sequencing data. The circular genome is 169,820 bp in size and comprises a pair of inverted repeat (IR) regions of 33,641 bp each, a large single-copy (LSC) region of 98,872 bp and a small single-copy (SSC) region of 3666 bp. The total GC content is 33.8%, while the corresponding values of the IR regions, LSC, and SSC and are 38.7%, 31.7% and 26.7%, respectively. The chloroplast genome contains 151 genes, including 91 protein-coding genes, eight ribosomal RNA genes and 52 transfer RNA genes. Two genes (ndhA and ndhB) are pseudogenized or lost in its cpDNA. The maximum-likelihood phylogenetic analysis showed a close relationship with P. armeniacum in Orchidaceae. Our findings provide useful information for phylogenetic and evolutionary research of Paphiopedilum species.